THE QUALITY AND TOTAL MICROBES OF BROILER CHICKEN IN TRADITIONAL MARKETS OF DENPASAR CITY - Luh Yuni Surya Antari; I N. Tirta Ariana; G. A. M. Kristina Dewi (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2017)
The purpose of this study was to determine the quality and total microbes of broiler at different location in the traditional markets of Denpasar City. This study used a completely randomized design (CRD) with four treatments. The treatments used in this study, broiler chicken sold at traditional markets in East (DT), North (DU), West (DB), and South of Denpasar (DS). The data obtained from this study were analyzed by analysis of variance. If there were significant differences (P <0,05) among the treatments, then continued with Duncan's multiple range test. The variables used in this study were carcass weight, cooking loss, drip loss, water holding capacity, water content, protein, fat, ash, and total microbes. The results showed that on the average, the highest carcass weight in DB treatment was 1.482 grams, with other treatments to get results not significantly different (P>0,05). The result of this study for variable drip loss, water content, protein, fat, and ash significantly different (P<0,05), then research result for cooking loss, and water holding capacity, were not significantly different (P>0,05). The research result for total microbies broiler chicken at traditional markets in Denpasar City have a range of 1,84 x 104 to 2,62 x 104 CFU /gram. The results were still normal when compared to SNI 7388: 2009 which states that the maximum amount that the content of TPC 1x106 CFU/gram. From these results, it was concluded that there were similarities quality of broiler chicken (carcass weight, cooking loss, water holding capacity, and total microbes), however, there were differences in the quality of broiler seen from drip loss, water content, protein, fat, and ash of broiler at traditional markets in Denpasar City.